Circulating Cytokines Could Not Be Good Prognostic Biomarkers in a Mouse Model of Amyotrophic Lateral Sclerosis - Moreno-Martínez, Laura; de la Torre, Miriam; Toivonen, Janne M.; Zaragoza, Pilar; García-Redondo, Alberto; Calvo, Ana Cristina; Osta, Rosario (Frontiers in Immunology, 2019)
Background: There is growing evidence of the role of inflammation in Amyotrophic Lateral Sclerosis (ALS) during the last decade. Although the origin of ALS remains unknown, multiple potential inflammatory biomarkers have been described in ALS patients and murine models of this disease to explain the progressive motor neuron loss and muscle atrophy. However, the results remain controversial. To shed light on this issue, we aimed to identify novel biomarkers of inflammation that can influence disease progression and survival in serial blood samples from transgenic SOD1G93A mice, a model of ALS. Methods: A cytokine array assay was performed to analyze protein expression of 97 cytokines in plasma samples from wildtype controls and transgenic SOD1G93A mice at asymptomatic stage. Subsequently, serial plasma samples were obtained from SOD1G93A mice at early symptomatic, symptomatic and terminal stages to monitor cytokine levels during disease progression through immunoassays. Comparisons of means of quantifiable cytokines between short-and long-lived mice were analyzed by unrelated t-test or Mann-Whitney U test. Relationships between cytokines levels and survival time were assessed using Pearson’s correlation analysis and Kaplan-Meier analysis. Results: A total of 16 cytokines (6Ckine, ALK-1, CD30 L, eotaxin-1, galectin-1, GITR, IL-2, IL-6, IL-10, IL-13, IL-17B R, MIP-1α, MIP-3β, RANKL, TROY and VEGF-D) were found dysregulated in transgenic SOD1G93A mice at asymptomatic stage compared with age-matched controls. Immunoassays of serial samples revealed positive expression of ALK-1, GITR and IL-17B R at P60 and P90 in mice with shorter survival. In addition, eotaxin-1 and galectin-1 levels were significantly increased at terminal stage in SOD1G93A mice that showed shorter survival time. Finally, levels of eotaxin-1, galectin-1, IL-2, IL-6, MIP-1α and TROY at P90 or endpoint negatively correlated with the longevity of transgenic mice. Conclusions: We demonstrated in the SOD1G93A model of ALS that increased levels of several cytokines were associated with a shorter lifespan. However, their role as prognostic biomarkers is unclear as their expression was very variable depending on both the disease stage and the subject. Nevertheless, cytokines may be potential therapeutic targets.